(-)-Epigallocatechin-3-gallate-mediated formation of myofibrillar protein emulsion gels under malondialdehyde-induced oxidative stress. (1st July 2019) - Lv, Yuanqi; Chen, Lin; Wu, Haizhou; Xu, Xinglian; Zhou, Guanghong; Zhu, Beiwei; Feng, Xianchao
Highlights: Low doses of malondialdehyde improved the quality of emulsion gels. High doses of malondialdehyde destabilized the structure of emulsion gels. Epigallocatechin-3-gallate weakened the gel structure under 6 mM malondialdehyde. Epigallocatechin-3-gallate improved the gel quality under 12 mM malondialdehyde. Abstract: The quality of meat products is influenced by protein oxidation. Understanding the effects of antioxidant polyphenols and oxidizing lipoperoxides on myofibrillar proteins is essential for controlling the quality of meat products. This study was designed to investigate the epigallocatechin-3-gallate (EGCG)-mediated formation of myofibrillar protein emulsion gels under malondialdehyde (MDA)-induced oxidative stress. Low MDA concentrations (3 and 6 mM) improved the water-holding capacity, strength, elasticity, and emulsifying properties of gels due to the enhanced protein-protein interactions via MDA. The addition of EGCG reduced the overall properties of the emulsion gel due to further modification of the proteins. At a high concentration of MDA (12 mM), there was excessive cross-linking and unfolding of myofibrillar proteins, which led to a compact gel structure, and reduced the overall properties of the gel. In this situation, the addition of EGCG protected myofibrillar proteins from modifications induced by MDA and improved the quality of emulsion gels.